2014
DOI: 10.1186/1757-2215-7-67
|View full text |Cite
|
Sign up to set email alerts
|

Association between intrafollicular concentration of benzene and outcome of controlled ovarian stimulation in IVF/ICSI cycles: a pilot study

Abstract: BackgroundSeveral studies have shown that exposure to benzene is associated to menstrual disorders, miscarriages and other disorders of the reproductive system. We performed an observational prospective pilot study to evaluate if levels of benzene in follicular fluid were correlated with response to controlled ovarian stimulation.MethodThirty-four normogonadotrophic women undergoing IVF were enrolled. Intra-follicular benzene levels were evaluated by chromatography/mass spectrometry. Based on median benzene le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The presence of genetic mutations or single nucleotide polymorphisms of Gn and their receptors can influence ovarian sensitivity to Gn stimulation (17,18). Apart from genotypic traits, there is also evidence to suggest that environmental contaminants and oxidative stress are involved in the hyporesponse pathogenesis (19)(20)(21). In this study, there were four multi-cycle patients in whom the FORT was still <0.30 after adjusting the OS protocol or Gn starting dose.…”
Section: Discussionmentioning
confidence: 74%
“…The presence of genetic mutations or single nucleotide polymorphisms of Gn and their receptors can influence ovarian sensitivity to Gn stimulation (17,18). Apart from genotypic traits, there is also evidence to suggest that environmental contaminants and oxidative stress are involved in the hyporesponse pathogenesis (19)(20)(21). In this study, there were four multi-cycle patients in whom the FORT was still <0.30 after adjusting the OS protocol or Gn starting dose.…”
Section: Discussionmentioning
confidence: 74%
“…Several previous studies have demonstrated the adverse influence of the environmental contaminants studied here on human and animal reproduction and fertility at various levels, including on ovarian hormones (Sirotkin and Harrath 2017). The negative correlation between ovarian follicular fluid benzene levels and the levels of plasma steroid hormones in women (Alviggi et al 2014) suggests that this contaminant can downregulate ovarian steroidogenesis, although it is not known whether benzene has a direct or indirect effect on steroidogenesis.…”
Section: Do Environmental Contaminants Benzene and Xylene Directly Afmentioning
confidence: 78%
“…Xylene has previously been shown to reduce P4 and estradiol levels in rat plasma, but did not affect the release of these hormones by rat ovaries (Ungváry et al 1981). Benzene and related oil-related contaminants are able to alter the release of GnRH and gonadotropins from the hypothalamus (Alviggi et al 2014;Stepanov et al 1990). These reports suggest that environmental contaminants can affect ovarian hormones probably by modulating upstream regulators of ovarian function.…”
Section: Do Environmental Contaminants Benzene and Xylene Directly Afmentioning
confidence: 98%
“…Environmental contaminants might also affect ovarian response during OS [29][30][31]. Thus, Alviggi et al in a retrospective study showed that elevated intrafollicular levels of benzene were associated with a decreased number of oocytes retrieved and embryos available for transfer [29], and it is currently believed that benzene leads to transduction deficiency in the FSHR. In another retrospective study, polychlorinated biphenyl congeners (PBC) in follicular fluid was associated with a decreased ovarian response during OS [32].…”
Section: Poseidon Groups 1 Andmentioning
confidence: 99%